Enhancing Students’ Writing Ability Through Error Analysis Concept: A Classroom Action Research - Irawansyah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research intends to find out if teaching students through the Error Analysis Concept (EAC), which covers omission, addition, mis-formation, and mis-ordering, improves their writing skills in any way. The study was conducted in two cycles using classroom action research as the research design. Planning, carrying out, observing, and reflecting were all included in each cycle. Twenty-six junior high school students in the second grade served as the study's subjects. Observation sheets and test writing were employed as data collection tools. The analysis of student writing improvements involved comparing scores between cycles. The outcome demonstrates that employing EAC improved the writing abilities of the students. This proves by comparing the score starting from pretest (56.56), cycle I (63.02) and Cycle II (68.52). As a result, the pre-research, cycle I, and cycle II mean scores for each type of error are 13.38, 7.54, and 5.50, respectively. It implies that students can reduce the amount of writing errors they make. In other words, that the students' writing skills have improved significantly. Furthermore, the process of teaching and learning is impacted by the application of the EAC. Since students' performance significantly improved and that incorporating the concept of error analysis into classroom activities had numerous advantages.